A taxonomic study on the species of the genus Diestramima Storozhenko (Orthoptera: Rhaphidophoridae; Aemodogryllinae) - Qin, Yanyan; Wang, Hanqiang; Liu, Xianwei; Li, Kai (Zootaxa, 2016)
A taxonomic study of the genus Diestramima Storozhenko, 1990 is presented. Eleven new species are described: D. excavata sp. nov., D. parabispinosa sp. nov., D. tibetensis sp. nov., D. guangxiensis sp. nov., D. subrectis sp. nov., D. curvicaudata sp. nov., D. beybienkoi sp. nov., D. triangulata sp. nov., D. brevis sp. nov., D. emeiensis sp. nov., D. conica sp. nov.. A key to the species of Diestramima is given.